A prospective study on implants installed with flapless-guided surgery using the all-on-four concept in the mandible - Landázuri-Del Barrio, R. A. [UNESP]; Cosyn, J.; De Paula, W. N. [UNESP]; De Bruyn, H.; Marcantonio, E. [UNESP] (Wiley, 2013)
Aim: Clinical data are scarce on flapless-guided surgery in the mandible using the all-on-four concept. In addition, limited documentation exists on the latter under immediate loading conditions with a pre-fabricated implant bridge. The aim was to provide detailed documentation focusing on clinical and radiographic outcome and complications. Material and methods: Sixteen systemically healthy non-smoking patients (10 women, 6 men, average age 59 years) with sufficient bone volume in the mandible were operated via flapless-guided surgery using the all-on-four concept. Clinical and radiographic data and complications were registered at 3, 6 and 12 months. Results: The overall implant survival rate was 90% with a trend for higher failure of short implants (P = 0.098). The mean bone level after 12 months of function was 0.83 mm with a maximum of 1.07 mm. Technical complications were common (15/16 patients). These mainly related to a misfit between the pre-fabricated prosthesis and abutment(s) (13/16 patients). Conclusion: If immediate loading of implants is pursued fabrication of the implant bridge should be based on actual impression of the implants at the time of surgery and not on their virtual position. © 2011 John Wiley & Sons A/S.
Keywords: All-on-four concept; Bone level; Flapless-guided surgery; Immediate loading; Technical complications